2023
DOI: 10.1007/s41809-022-00117-9
|View full text |Cite
|
Sign up to set email alerts
|

Word learning in ASD: the sensorimotor, the perceptual and the symbolic

Abstract: Word learning requires successful pairing of form and meaning. A common hypothesis about the process of word learning is that initially, infants work on identifying the phonological segments corresponding to words (speech analysis), and subsequently map those segments onto meaning. A range of theories have been proposed to account for the underlying mechanisms and factors in this remarkable achievement. While some are mainly concerned with the sensorimotor affordances and perceptual properties of referents out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 115 publications
2
2
0
Order By: Relevance
“…Furthermore, potential problems at higher levels of abstraction in spatial representation may lead to the observed problems in applying the shape‐bias in word learning in autism. This speculation aligns with the proposal that weakened abstraction and symbolic use may explain the observed semantic problems in word learning in autism (Vulchanova et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, potential problems at higher levels of abstraction in spatial representation may lead to the observed problems in applying the shape‐bias in word learning in autism. This speculation aligns with the proposal that weakened abstraction and symbolic use may explain the observed semantic problems in word learning in autism (Vulchanova et al, 2023).…”
Section: Discussionsupporting
confidence: 90%
“…A promising perspective is to acknowledge the presence of distinct components in the process underlying SL., It has been suggested that statistical learning can be broken down into two dissociable components: (1) perceptual binding of individual stimulus units into integrated composites and (2) storing those integrated representations for later use [ 76 ]. Such a view is consistent with the evidence from word learning in children, whereby the initial stages involve speech segmentation and consolidation of the phonological form, which can subsequently be used for the purposes of mapping onto content [ 20 , 77 , 78 ]. These two respective components of SL can, and should, be studied independently with specifically designed tasks.…”
Section: Discussionsupporting
confidence: 78%
“…This is not surprising, given the central role of the auditory modality in oral language skills and, specifically, in word segmentation. The role of skills in audio-visual binding is also quite consistent with the process of mapping auditory information (phonological form) to visually available referents corresponding to word meanings, which is an essential step in word learning [ 20 ]. The reviewed studies attest not only concurrent or predictive relationship between SL and vocabulary, but also attest an association in the opposite direction, namely between existing vocabulary knowledge and SL skills.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation